1994
DOI: 10.1111/j.1365-2125.1994.tb04360.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of bradykinin‐induced vasodilation in human forearm vasculature by icatibant, a potent B2‐receptor antagonist.

Abstract: 1 The effect of icatibant Thi5, Oic8]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 30 publications
4
57
0
Order By: Relevance
“…20 The present study extends these observations on the role of BK in vascular physiology. As reported previously in humans, 9 we observed that B 2 receptor antagonism specifically blocked BK-induced vasodilation; in addition, we observed that B 2 receptor antagonism blocked the effect of BK on tPA release from the forearm vascular endothelium.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…20 The present study extends these observations on the role of BK in vascular physiology. As reported previously in humans, 9 we observed that B 2 receptor antagonism specifically blocked BK-induced vasodilation; in addition, we observed that B 2 receptor antagonism blocked the effect of BK on tPA release from the forearm vascular endothelium.…”
Section: Discussionsupporting
confidence: 72%
“…We and others have shown that this dose inhibits the forearm vasodilator response to intra-arterial BK without affecting systemic blood pressure or HR. 9,10 Thirty minutes after completion of the HOE 140 infusion, intra-arterial infusions of SNP and BK were repeated. Pilot studies demonstrated that there was no tachyphylaxis to BK over this time interval.…”
Section: Protocol 1: Effect Of Bk Receptor Antagonismmentioning
confidence: 99%
“…15 The study confirms prior studies with HOE 140 indicating that endogenous BK does not contribute to resting vascular tone. 12,19,21 However, this is the first study to demonstrate that ACE inhibition increases constitutive forearm endothelial t-PA release through an effect on endogenous BK.…”
Section: Discussionmentioning
confidence: 98%
“…This dose of HOE 140 has no effect on systemic blood pressure or heart rate, but blocks both the vasodilator and t-PA responses to infused BK for at least 3 hours. 11,19 FBF measurements and arterial and venous sampling were repeated after HOE 140. At this time, enalaprilat was infused in the brachial artery at a rate of 5 g/min.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…This dose has been shown to significantly blunt the vasodilatory response to intra-arterial bradykinin. 51 BP was determined using an automated oscillometric recording device every 5 min during the study (Dinamap, Critikon, Carlsbad, CA), using the average of three readings at each time point. Blood for biochemical analysis was collected 1 h before dialysis (T ϭ Ϫ60), at initiation of dialysis (T ϭ 0), 15 and 30 min after initiation of dialysis (T ϭ 15 and 30 min), at termination of dialysis (T ϭ 4 h), and 2 h after termination of dialysis (T ϭ 6 h).…”
Section: Study Protocolmentioning
confidence: 99%